Conflicts Causing a Conflict of Spiritual Interests and Ideological Methods and Means of Their Elimination - Kholmirzayeva Manzura Abdimuratovna (International Journal on Integrated Education, 2023)
It contains a number of analytical information about conflicts causing the conflict of spiritual interests in this country and the ideological methods and means of their elimination.